Guidelines for the first-line treatment of restless legs syndrome/Willis–Ekbom disease, prevention and treatment of dopaminergic augmentation: a combined task force of the IRLSSG, EURLSSG, and the RLS-foundation - Garcia-Borreguero, Diego; Silber, Michael H.; Winkelman, John W.; Högl, Birgit; Bainbridge, Jacquelyn; Buchfuhrer, Mark; Hadjigeorgiou, Georgios; Inoue, Yuichi; Manconi, Mauro; Oertel, Wolfgang; Ondo, William; Winkelmann, Juliane; et al. (Sleep medicine, 2016)
•Prevention of augmentation may be started by considering using medications such as α2δ ligands for initial RLS treatment.•If treatment is initiated with dopaminergic drugs, the dose should be kept low and not exceed that recommended for RLS.•Patients with low iron stores should be given appropriate iron supplementation.•Treatment of existing augmentation should be initiated by eliminating/correcting extrinsic exacerbating factors where possible.•In cases of mild augmentation dopamine agonist therapy can be continued by dividing or advancing the dose.•For severe augmentation the patient can be switched to an α2δ ligand or to rotigotine, noting that rotigotine may also produce augmentation at higher doses with long-term use.•In severe cases of augmentation a high-potency opioid may be considered, bypassing α2δ ligands and rotigotine. A Task Force was established by the International Restless Legs Syndrome Study Group (IRLSSG) in conjunction with the European Restless Legs Syndrome Study Group (EURLSSG) and the RLS Foundation (RLS-F) to develop evidence-based and consensus-based recommendations for the prevention and treatment of long-term pharmacologic treatment of dopaminergic-induced augmentation in restless legs syndrome/Willis–Ekbom disease (RLS/WED). The Task Force made the following prevention and treatment recommendations: As a means to prevent augmentation, medications such as α2δ ligands may be considered for initial RLS/WED treatment; these drugs are effective and have little risk of augmentation. Alternatively, if dopaminergic drugs are elected as initial treatment, then the daily dose should be as low as possible and not exceed that recommended for RLS/WED treatment. However, the physician should be aware that even low dose dopaminergics can cause augmentation. Patients with low iron stores should be given appropriate iron supplementation. Daily treatment by either medication should start only when symptoms have a significant impact on quality of life in terms of frequency and severity; intermittent treatment might be considered in intermediate cases. Treatment of existing augmentation should be initiated, where possible, with the elimination/correction of extrinsic exacerbating factors (iron levels, antidepressants, antihistamines, etc.). In cases of mild augmentation, dopamine agonist therapy can be continued by dividing or advancing the dose, or increasing the dose if there are breakthrough night-time symptoms. Alternatively, the patient can be switched to an α2δ ligand or rotigotine. For severe augmentation the patient can be switched either to an α2δ ligand or rotigotine, noting that rotigotine may also produce augmentation at higher doses with long-term use. In more severe cases of augmentation an opioid may be considered, bypassing α2δ ligands and rotigotine.